tDCS peripheral nerve stimulation can enhance passive avoidance learning in rats - van Boekholdt, Luuk; Kerstens, Silke; Decloedt, Kaydee; Mc Laughlin, Myles (Frontiers in Neuroscience, 2025)
Transcranial direct current stimulation (tDCS) is being considered as a treatment for many psychiatric and neurological disorders. Rodent models of tDCS have been used in several behavioral tasks to demonstrate the technique’s benefits in improving memory and learning. Recent research suggests that peripheral nerve stimulation in tDCS may be responsible for some of its effects. In this work, we first aimed to repeat a previously reported tDCS effect of improved passive avoidance task (PAT) learning in a minimally restrictive rat model and investigate whether peripheral nerve stimulation contributed to these effects by using two additional stimulation groups in which the electric field in the brain (transcranial-only tDCS) and skin (transcutaneous-only tDCS) were separated. Analysis revealed that, at 0.25 mA, none of the stimulation conditions significantly improved PAT learning compared to sham. This non-replication experiment calls for more research to investigate whether tDCS at 0.25 mA can truly improve PAT learning in rats. In a subsequent experiment, we aimed to investigate the effects of transcutaneous-only tDCS at 2 mA, an amplitude more relevant to tDCS in humans. We found that 30 min of DC stimulation at 2 mA, with the cathodal electrode implanted over the third occipital nerve, improved PAT learning. This indicates that DC stimulation of peripheral nerves is capable of modulating learning and memory and supports the theory that peripheral nerve stimulation may contribute to some observed effects of tDCS. More research is necessary to investigate the behavioral and neurophysiological effects of DC peripheral nerve stimulation, and its contribution in tDCS effects observed in animals and humans.